Pengembangan Aplikasi Perangkat Bergerak Sistem Informasi Manajemen Produk Transaksi dan Keuangan UMKM di Kota Malang berbasis Android - Yohannes Sebastian Sibarani; Agi Putra Kharisma; Riswan Septriayadi Sianturi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One of the problems experienced by MSMEs is conventional recording. Conventional recording problem causes a discrepancy in the recording of production and transactions of goods. This situation can make it difficult for MSMEs to compete with their competitors. The MSME information system can encourage an increase in the competitiveness of an MSME compared to its competitors. This study aims to develop a mobile application for MSME information systems in the city of Malang. The MSME information system was developed using the SDLC waterfall, the Android operating system, and the Firebase data storage service. This research was conducted in 4 stages, namely needs analysis, design, implementation and testing. The needs analysis carried out resulted in 17 functional requirements and 3 non-functional requirements. The design stage produces activity diagrams, sequence diagrams, class diagrams, pseudocode, data design, and interface design. In the implementation phase, the database, program code and interface are implemented. In the testing phase, 4 tests were carried out, namely validation with black box, usability with SUS, portability (Android version 9.0, 10.0,11.0 and internet connectivity), and localization (translation). Blackbox testing shows 100% valid results for functional requirements. Usability testing with the SUS method produces an average score of 89.5 (best imaginable). Compatibility testing and localization testing show valid results. The results of this study can make it easier for MSME actors to record production and transactions of goods and reduce the risk of recording mismatches.